MELACAK AKAR IDEOLOGI PURITANISME ISLAM: SURVEI BIOGRAFI ATAS “TIGA ABDULLAH” - Mutohharun Jinan (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2014)
This paper examined the variant of Islamic movement with biographical point of view to three muslims figures, namely Abdullah Sungkar (the founder of Jemaah Islamiyah), Abdullah Marzuki (the founder of Majelis Pengajian Islam), and Abdullah Thufail Saputro (the founder of Majelis Tafsir Al-Qur’an). They have been known as the “Triple A”. They have been being very influential in the dynamics of Islam in Surakarta since the 1970s until today. They have worked together to spread the teachings of Islam in many religious activities. Applying qualitative approach and using documentation study, it was founded that due to many differences in intellectual backgrounds and ideological orientations of each other that lead them to choose different strategies to realize the ideal Islamic society. The first figure selected resistant position and fight against the hegemony of the state, the second figure chose neutral and do not care about political issues, and the third figure to choose the path of accommodative policy of the state.